2020
DOI: 10.1093/humrep/deaa194
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of markers of endotoxemia in women with polycystic ovary syndrome

Abstract: STUDY QUESTION Is polycystic ovary syndrome (PCOS) associated with an elevation of markers of endotoxemia? SUMMARY ANSWER In women with PCOS serum levels of lipopolysaccharides (LPS), the LPS to high-density lipoprotein (HDL) ratio and LPS-binding protein (LBP) are significantly greater than those of normal control subjects. WHAT IS KNOWN ALREADY Mononuclear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…PCOS patients are more prone to intestinal flora imbalance and microbiota abnormalities caused by enteral malnutrition, which can producing metabolic endotoxin (LPS) that invades the intestinal wall and aggravates systemic inflammation (36). Therefore, we used LPS as a classic inducer to activate NF-kB pathway to simulate the similar inflammatory status of PCOS patients (19).…”
Section: Discussionmentioning
confidence: 99%
“…PCOS patients are more prone to intestinal flora imbalance and microbiota abnormalities caused by enteral malnutrition, which can producing metabolic endotoxin (LPS) that invades the intestinal wall and aggravates systemic inflammation (36). Therefore, we used LPS as a classic inducer to activate NF-kB pathway to simulate the similar inflammatory status of PCOS patients (19).…”
Section: Discussionmentioning
confidence: 99%
“…As reported, the increased circulating LPS is deemed as a risk factor for PCOS. Duleba et al demonstrated that LPS profoundly increased the expression of key genes in androgen synthesis and contributed to hyperandrogenemia ( Banaszewska et al, 2020 ). To some extent, this helps explain the reason why the administration of SGD could ameliorate the hyperandrogenism in PCOS rats by reducing the LPS level.…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, the downstream mediators [such as nuclear factor-κB (NF-κB) and phosphatidylinositol 3-kinase (PI3K)] were activated and numerous pro-inflammatory cytokines (e.g., tumor necrosis factor (TNF)-α, IL-1β and IL-18) were released consequently ( Liu et al, 2010 ). Of note, the elevated serum level of LPS had been observed in women with PCOS and the index was regarded as a risk factor of PCOS ( Banaszewska et al, 2020 ). The LPS-induced inflammatory response occurs in multiple tissues including ovarian theca.…”
Section: Introductionmentioning
confidence: 99%
“…A cross-sectional study of 144 women found elevated markers of endotoxemia in women with PCOS compared with healthy ovulatory women. Women with PCOS had significantly higher mean LPS ( P =0.045), LPS to high-density lipoprotein ratio ( P =0.007), and LPS-BP ( P =0.01) [ 50 ]. All measures of endotoxemia correlated independently and positively with the inflammatory markers and ovarian volume.…”
Section: Resultsmentioning
confidence: 99%
“…All measures of endotoxemia correlated independently and positively with the inflammatory markers and ovarian volume. Taken together, the findings of these two studies suggest that women with PCOS may exhibit a pro-inflammatory state related to elevated markers of endotoxemia, including LPS and LPS-BP [ 45 , 50 ].…”
Section: Resultsmentioning
confidence: 99%